Multi-scenario simulation of ecosystem service value for optimization of land use in the Sichuan-Yunnan ecological barrier, China - Chen Li (Elsevier, 2021)
Key ecological function areas are responsible for protecting and restoring ecosystems and alleviating regional ecological deterioration. Revealing the inherent relationship between land use/cover (LULC) change and ecosystem service value (ESV) in such areas is of great significance for sustainable development. We used LULC and other data from 2000, 2010, and 2018 to analyze the spatiotemporal evolution of ESV in China’s Sichuan-Yunnan Ecological Barrier based on six LULC types: Farmland, Forest, Grassland, Water, Built-up land, and Other. With the goal of maximizing both ESV and economic benefits, we used coupled gray multi-objective optimization (GMOP) and patch-generating land-use simulation (PLUS) models to assess three scenarios (business-as-usual, BAU; ecological development priority, EDP; and ecological and economic balance, EEB) in terms of the spatial distribution and optimization of LULC structure in 2026. The study area was dominated by Forest and Grassland, with major LULC changes from 2000 to 2018 mainly deriving from transfers between Farmland, Forest, and Grassland along with Farmland conversion to Built-up land. ESV trended upward during the study period, mainly due to contributions from Forest and Water. Under EDP scenario in 2026, the expansion Built-up land was eased, which expansion area is the smallest among the 3 scenarios at 643.03 km2, the Forest area increased by 673.80 km2, the overall LULC structure was improved, and the total ESV increased by 2.502 billion yuan. Under EEB scenario, Forest area decreased by 405.95 km2, but the economic benefits increased remarkably, showing the effect of supporting larger-scale economic growth with less land resource consumption. Under EDP scenario, ESV changes were most dramatic at local scales. The use of coupled GMOP-PLUS models for LULC optimization allowed improved assessment of social, economic, and environmental factors and provided a new way to address key technical problem in land-use planning in large-scale ecological function areas.